SIGNIFIKANSI LEMBAGA AL-ḤISBAH DALAM SISTEM EKONOMI ISLAM - Khairuddin Wahid (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2018)
If the teachings of neoclassical economic systems minimize the role of the state in the market, and conversely the teaching of socialist economic systems maximizes the role of the State in the market, Islamic economic systems teach that markets, countries and individuals are in balance (iqtiṣād / equilibrium). This means that for Islamic economic systems, the State is in a unified system. However, Islamic economic systems guarantee a free market mechanism, where sellers and buyers are free to compete fairly in terms of equity. To guarantee the sustainability of this market fairly, from the outset the Messenger of Allah saw attention to the market by conducting an investigation into the market. This sunna is preserved by friends and the Islamic world, which in turn is transformed into an institution of ratio. After observing the objectives, principles, and characteristics of Islamic economic systems, it turns out that the existence of this market watchdog is a necessity, as a logical consequence of the Islamic economic system it self.